Knowledge and Attitudes in Pain Relief Management Among Private Hospital Nurses - Rosnida Abu Bakar; Yee Bit-Lian; Puteri-AdistiJamil (Talenta Publisher, 2021)
For both nurses and patients, effective pain relief management is critical. Relieving patients’ pain and suffering are considered the responsibility of nurses. A cross-sectional descriptive study was conducted. The Nurses Knowledge and Attitude Regarding Pain Questionnaire was used to measure the nurses’ level of knowledge and attitude toward pain assessment and management. The results showed a lack of knowledge among nurses regarding pain relief management. It started with the fundamental question regarding the usage of the vital sign as reliable indicators of the intensity of a patient’s pain. 90.6% (145) of the nurses answered ‘True’, but the correct answer was ‘False’, and only 9.4% (15) of the nurses gave the correct answer. We found out that 60% (96) of nurses believed that patients should not receive opioid treatment even if they are in pain. This study discovered that the level of knowledge on pain relief management among nurses in the private hospital was inadequate. The patients should receive appropriate treatment to relieve the pain regardless of their history of substance abuse. This perception on the nurses could prevent some of the patients from their right to being pain-free.